2011
DOI: 10.1111/j.1447-0756.2011.01585.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐grade appendiceal mucinous neoplasm with disseminated peritoneal adenomucinosis involving the uterus, mimicking primary mucinous endometrial adenocarcinoma: A case report

Abstract: We present a patient with a low-grade appendiceal mucinous neoplasm, resulting in disseminated peritoneal adenomucinosis (pseudomyxoma peritonei) with uterine involvement, and mimicking primary mucinous endometrial adenocarcinoma. On immunohistochemistry, neoplastic glands were cytokeratin 7-negative and cytokeratin 20-positive, indicating a gastrointestinal origin rather than a primary ovarian mucinous neoplasm. A diagnosis of uterine metastasis of appendiceal origin was made, based on the constellation of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Samet et al (4) reported a case similar to Moore's second case, in that epithelium histologically and immunohistochemically consistent with intestinal derivation was admixed with normal endometrial and endocervical epithelium on microsopic examination of the uterus of a patient with known LAMN. Tanaka et al (5) reported a case with similar findings but with invasion of the myometrium in a woman with a diagnosis of LAMN several years earlier. In all of these cases, the differential diagnosis is between secondary involvement by LAMN, a primary intestinal-type neoplasm at these sites, or possibly intestinal metaplasia in the noninvasive cases.…”
Section: Pseudomyxoma Endometriimentioning
confidence: 62%
See 2 more Smart Citations
“…Samet et al (4) reported a case similar to Moore's second case, in that epithelium histologically and immunohistochemically consistent with intestinal derivation was admixed with normal endometrial and endocervical epithelium on microsopic examination of the uterus of a patient with known LAMN. Tanaka et al (5) reported a case with similar findings but with invasion of the myometrium in a woman with a diagnosis of LAMN several years earlier. In all of these cases, the differential diagnosis is between secondary involvement by LAMN, a primary intestinal-type neoplasm at these sites, or possibly intestinal metaplasia in the noninvasive cases.…”
Section: Pseudomyxoma Endometriimentioning
confidence: 62%
“…Much more rarely, spread of LAMN to other gynecologic sites has been reported, including the fallopian tubes (7), endometrium, and endocervix (3)(4)(5).…”
Section: Pseudomyxoma Endometriimentioning
confidence: 99%
See 1 more Smart Citation
“…Th e plethora of confl icting evidence in literature [7][8][9][10][11][12][13][14][15][16][17] and the reconciliation with the fact that both tumors appear similar in morphology and IHC expression regardless of origin raises important research questions. First; if these tumors are so mysteriously similar in morphology and IHC expression, do they have a similar biological behavior?…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal adenocarcinoma, especially mucinous adenocarcinoma, is notorious for its spread to adjacent organs and forms the fistula to colon [6], uterus [7], and skin [8]. It is uncommon that an appendiceal adenocarcinoma penetrates into the bladder.…”
Section: Introductionmentioning
confidence: 99%